How to interview & hire the right people - Carline, Stephen (Boulder : CareerTrack Publications, 1993)
Volume one helps to lay the groundwork before meet with a candidate. Volume two and three, learn step-by-step how to conduct an effective interview
Trainers: Stephen Carline
Keywords: Interviewing; Interviews; Employment interviewing